The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/mec.16309
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale genetic diversity and putative ecotypes of oxymonad protists coinhabiting the hindgut of Reticulitermes speratus

Abstract: The hindgut of lower termites is generally coinhabited by multiple morphologically identifiable protist species. However, it is unclear how many protist species truly coexist in this miniaturized environment, and moreover, it is difficult to define the fundamental unit of protist diversity. Species delineation of termite gut protists has therefore been guided without a theory‐based concept of species. Here, we focused on the hindgut of the termite Reticulitermes speratus, where 10 or 11 morphologically distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Before the lysis step, a sterile stainless-steel bead (5 mm, Qiagen, Hilden, Germany) was placed in each tube, and the sample tubes were attached to a Vortex Adapter (24 tubes, Qiagen) and homogenized using a vortex mixer (Vortex-GENIE 2, Scientific Industries, Bohemia, NY, USA) at maximum speed for 10 min. The V3–V4 regions of 18S rRNA genes were PCR-amplified using the oxymonad-specific primers [40], with some modifications (RsOx_Sc432: 5′-GCGCAAATTACCCACTGGCA-3′; RsOx_Sc789_2Y: 5′-TTCAGCYGCGARACGCCYTG-3′), and the parabasalid-specific primers [23] (Par_18S-F: 5′-GCAGCAGGCGYGAAAC-3′; Par_18S-R: 5′-CCTACTCTCGCYCTTGATCG-3′). The PCR mixture contained 1 μL of whole-gut DNA, 1× HF buffer, 0.2 mM dNTPs, 0.5 μM primer set, and 0.4 U of Phusion high-fidelity DNA polymerase (New England Biolabs, Ipswich, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the lysis step, a sterile stainless-steel bead (5 mm, Qiagen, Hilden, Germany) was placed in each tube, and the sample tubes were attached to a Vortex Adapter (24 tubes, Qiagen) and homogenized using a vortex mixer (Vortex-GENIE 2, Scientific Industries, Bohemia, NY, USA) at maximum speed for 10 min. The V3–V4 regions of 18S rRNA genes were PCR-amplified using the oxymonad-specific primers [40], with some modifications (RsOx_Sc432: 5′-GCGCAAATTACCCACTGGCA-3′; RsOx_Sc789_2Y: 5′-TTCAGCYGCGARACGCCYTG-3′), and the parabasalid-specific primers [23] (Par_18S-F: 5′-GCAGCAGGCGYGAAAC-3′; Par_18S-R: 5′-CCTACTCTCGCYCTTGATCG-3′). The PCR mixture contained 1 μL of whole-gut DNA, 1× HF buffer, 0.2 mM dNTPs, 0.5 μM primer set, and 0.4 U of Phusion high-fidelity DNA polymerase (New England Biolabs, Ipswich, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The rarefied reads were combined (i.e., 470,000 and 450,000 read pairs in total for Oxymonadida and Parabasalia, respectively), followed by denoising, merging of paired-end reads, identification of chimeras, and sorting into single-nucleotide-level amplicon sequence variants (ASVs) using dada2. ASVs with a relative abundance of <0.1% of the total reads in a given sample and those detected in only one sample were excluded based on previous control experiments [40]. ASVs were subsequently grouped into operational taxonomic units (OTUs) based on 97% nucleotide similarity using the DECIPHER package in R [43].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches have revealed cryptic protist species in many termites, even in such well‐studied termites as Coptotermes formosanus (Nishimura et al ., 2020; Jasso‐Selles et al ., 2020). In a ground‐breaking study that combined single‐cell 18S sequencing with whole‐gut metabarcoding data, 33 species‐level lineages of oxymonads were counted in Reticulitermes speratus , far higher than the 11 morphospecies described from the same host (Koidzumi, 1921; Igai et al ., 2022). Molecular studies occasionally reveal lower diversity than was reported by morphology (Strassert et al ., 2009), but on the whole, termite protist diversity is higher when informed by sequence data than when informed by morphology alone.…”
Section: The Protistsmentioning
confidence: 99%
“…Only three oxymonad phylotypes have been characterised from H. sjostedti so far, despite the recognition of six morphotypes. It seems likely that many additional phylotypes will be uncovered by a more focused analysis, given that molecular data have recently demonstrated a very high diversity of Pyrsonympha and Dinenympha in Reticulitermes speratus (Igai et al ., 2022).…”
Section: The Hosts and Their Symbiontsmentioning
confidence: 99%